Socio-medical burden of managing a Nigerian child with 46XY male disorder of sex differentiation: A Case Report - Oba-Daini OO; Fetuga MB; Ogundele IO; Nwokoro CC; Olatunji AA; Ogunfowora OB (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2019)
Phenotypic expression of the male internal and external genitalia is due largely to the interplay between the proper differentiation of the bipotential gonad, the production of testosterone from the Leydig cells and the response of the undifferentiated external genitalia to Dihydrotestosterone. When any of the pathways involved in the mechanisms described above are distorted, it results in the 46XY Disorder of Sex Differentiation (DSD). The incidence of 46 XY DSD ranges from 20 to 41% among the cases of Disorder of Sex Differentiation (DSD) in Nigeria, though there is a paucity of data on this condition. This report describes an under-virilized genetically male child who presented with ambiguous genitalia in the neonatal period and was subsequently diagnosed as SRY positive 46 XY DSD with reduced testosterone synthesis. This report is necessitated by the need to create awareness and highlight the relevant medico-social challenges in the management of DSD in a resource-poor setting.